Pengembangan Website dan Sistem Informasi Desa (SID) Prampelan Kecamatan Karangrejo Kabupaten Magetan dalam Rangka Pencapaian Tujuan Pembangunan Berkelanjutan (SDGs) - Wahyu Mahesa Miarta; Gilang Gusti Aji; Eko Pamuji; Herma Retno Prabayanti; Ade Firmannandya; Jauhar Wahyuni (Abimanyu : Jornal of Community Engagement, 2025)
This community service aims to develop a Village Information System (SID) in Prampelan Village, Karangrejo District, Magetan Regency, to support the achievement of Sustainable Development Goals (SDGs) by increasing information accessibility and village management efficiency. This website-based SID is built with an open-source platform that supports the management of various village information ranging from development programs, public services, to community activities digitally. The methods used are Science and Technology Diffusion and training, involving active participation from village officials and local communities. The results of the community service show an increase in access to information for the community, as well as an increase in the skills of village officials in managing SID. This program is expected to be a model for other villages to utilize technology in achieving sustainable development goals..Keywords: Village Information System, SDGs, Information Accessibility, Village Management, Open-source CMS